The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12889-020-08637-1
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of vaccine wastage in two different geographic contexts under the universal immunization program in India

Abstract: Background: Government of India is introducing new and relatively costly vaccines under immunization program. Monitoring of vaccine wastage is needed to guide the program implementation and forecasting. Under pilot introduction of rotavirus vaccine in two districts both 5-and 10-doses vials were used, which was considered as an opportunity for documenting the wastage. The wastage rates for other routine vaccines were also documented. Methods: A survey conducted in two districts (Kangra, Himachal Pradesh and Pu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
3
10
2
Order By: Relevance
“… The number of doses in each vial [ 99 ]: WHO calculated the wastage rates for a single dose, 2 or 5-dose, and 10 or 20-dose were 5%, 10%, and 25% if the opened vial can be stored and reused in later sessions [ 98 ]. This has also been partially verified by Indian situations [ 153 ]. The no-show behaviour of the population [ 154 ]: Although some residents signed up for vaccination, not all of them would show up to get vaccines due to multiple reasons.…”
Section: Lessons and Opportunities For Future Pandemicssupporting
confidence: 55%
See 1 more Smart Citation
“… The number of doses in each vial [ 99 ]: WHO calculated the wastage rates for a single dose, 2 or 5-dose, and 10 or 20-dose were 5%, 10%, and 25% if the opened vial can be stored and reused in later sessions [ 98 ]. This has also been partially verified by Indian situations [ 153 ]. The no-show behaviour of the population [ 154 ]: Although some residents signed up for vaccination, not all of them would show up to get vaccines due to multiple reasons.…”
Section: Lessons and Opportunities For Future Pandemicssupporting
confidence: 55%
“…The number of doses in each vial [ 99 ]: WHO calculated the wastage rates for a single dose, 2 or 5-dose, and 10 or 20-dose were 5%, 10%, and 25% if the opened vial can be stored and reused in later sessions [ 98 ]. This has also been partially verified by Indian situations [ 153 ].…”
Section: Lessons and Opportunities For Future Pandemicssupporting
confidence: 55%
“…This is similar to the findings from other studies. [ 15 19 ] This may be because of the fact that the lyophilized vaccines need to be discarded within 4 h after reconstitution. [ 7 ] But, however BCG and Measles both behaved differently, for BCG overall wastage was within permissible limits at District Level but not so at CHC and SC, whereas Measles had wastage within permissible limits at all service delivery points despite the fact that both being reconstituted vaccines and have to be discarded after 4 h. A similar finding that substantially higher wastage of lyophilized vaccines compared to liquid ones was observed in UNICEF study.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted between two locations of Kangra, Himachal Pradesh and Pune, Maharashtra showed that overall wastage rates for almost all vaccines were higher in Kangra district (BCG 37.1%, DPT 32.1%, Measles 32.2%, OPV 50.8%, TT 34.1% and pentavalent 18.4%) than that of Pune district (BCG 35.1%, DPT 25.4%, Measles 21.7%, OPV 14.3%, TT 23.1% and pentavalent 13.2%. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…In Kangra the wastage rates for different types of vaccines were: BCG 37.1%, DPT 32.1%, Measles 32.2%, OPV 50.8%, TT 34.1% and pentavalent 18.4%. While in Pune district the reported rates for vaccines wastage were: BCG 35.1%, DPT 25.4%, Measles 21.7%, OPV 14.3%, TT 23.1% and pentavalent 13.2% [ 2 ]. To assess missed opportunities for vaccination, the vaccine wastage rates for different categories were assessed in Cambodia and the assessment had found in 100 randomly selected health facilities in 24 districts the wastage rate for single dose vaccine was 4% while for multiple dose vaccines it was as high as 60% [ 3 ].…”
mentioning
confidence: 99%